A qualitative study assessing patient perspectives in the process of decision-making on disease modifying therapies (DMT's) in multiple sclerosis (MS). - Archibald de Ceuninck van Capelle; Hanneke van der Meide; Frans J H Vosman; Leo H Visser (PLoS ONE, 2017)
Physicians commonly advise patients to begin disease modifying therapies (DMT's) shortly after the establishment of a diagnosis of Multiple Sclerosis (MS) to prevent further relapses and disease progression. However, little is known about the meaning for patients going through the process of the diagnosis of MS and of making decisions on DMT's in early MS.To explore the patient perspective on using DMT's for MS. Methods: Ten participants with a recent (< 2 years) relapsing-remitting MS diagnosis were interviewed. Seven of them were using DMT's at the time of the interview. All interviews were transcribed and analyzed using a hermeneutical-phenomenological approach.The analysis revealed the following themes: (1) Constant confrontation with the disease, (2) Managing inevitable decline, (3) Hope of delaying the progression of the disease, and, (4) The importance of social support. The themes show that patients associate the recommendation to begin DMT's (especially injectable DMT's) with views about their bodies as well as their hopes about the future. Both considering and adhering to treatment are experienced by patients as not only matters of individual and rational deliberation, but also as activities that are lived within a web of relationships with relatives and friends.From the patient perspective, the use of DMT's is not a purely rational and individual experience. More attention to the use of DMT's as relational and lived phenomena will improve the understanding of the process of decision-making for DMT's in MS.